Digital Transformation of Islamic Education: Trends, Challenges, and Future Research Directions - Adiyono, Adiyono (Kawanua International Journal of Multicultural Studies, 2020)
The digital transformation of Islamic education has become an increasingly important issue, particularly in light of the rapid technological acceleration experienced after 2020. However, limited attention has been given to understanding how Islamic educational institutions prepared for digital transformation prior to the pandemic. This study aims to systematically examine research trends, challenges, and institutional readiness related to digital transformation in Islamic education during the period 2015–2020. The main problem addressed in this paper is the fragmented and descriptive nature of existing studies, which lack comprehensive synthesis and policy-oriented analysis. This study employed a systematic literature review (SLR) approach, following the PRISMA framework. Data were collected from Google Scholar, Moraref, SINTA, and ERIC, resulting in 32 peer-reviewed journal articles that met the inclusion criteria. The selected studies were analyzed using thematic analysis to identify dominant patterns related to digital technologies, pedagogical practices, institutional readiness, and challenges. The findings reveal that digital transformation in Islamic education during this period was predominantly at an early and instrumental stage, focusing mainly on basic technologies such as e-learning platforms and learning management systems. Institutional preparedness was generally low, with digital initiatives largely driven by individual teachers rather than strategic policies or leadership frameworks. These results highlight the need for value-based management, leadership support, and human-centered digital strategies to ensure sustainable digital transformation in Islamic education.